Capitalist Realism: Is There No Alternative? - Fisher, Mark (UK; Zero Books, 2009)
After 1989, capitalism has been presented as the only realistic political-economic system. This work explores its effects on work, culture, education and mental health, and possible alternatives.
English
Keywords: Capitalism- real life implications; HB501 Economic Theory. Demography- Capital. Capitalism-